IS BP LOAD ON AMBULATORY MONITORING A PREDICTOR OF TARGET ORGAN DAMAGE IN YOUTH? THE SHIP AHOY STUDY. (April 2021) - Hamdani, Gilad; Ferguson, Michael; Lande, Marc; Meyers, Kevin; Samuels, Joshua; Flynn, Joseph T.; Urbina, Elaine M.
Abstract : Objective: Ambulatory BP monitoring (ABPM) is increasingly utilized for the diagnosis of hypertension (HTN). Pediatric guidelines consider BP load (% of reading above the 'normal' threshold) in risk-stratification of the ABPM phenotype. We sought to determine if load was an independent predictor of target organ damage (TOD) in youth. Figure. No caption available. Design and method: Casual BP, ABPM, anthropometrics, echo for LV mass index (LVMI), systolic strain, diastolic function (E'/e' ratio) and pulse wave velocity (PWV) for arterial stiffness (PWV) were measured in 367 adolescents (mean 15.6 + 1.7 years, 63% white, 58% male). ABPM was performed with Ontrak device (Spacelabs Inc., Snoqualmie, WA). Subjects were stratified by load (low <25% = 215, mid 25-<50% = 62, high >=50% =47) according to sex- and height-specific pediatric cut points. ANOVA was used to evaluate differences in CV risk factors and TOD across load groups. General linear models were used to evaluate load as an independent predictor of TOD after adjusting age, demographics, body mass index (BMI), and mean daytime SBP on ABPM. Results: There was a graded increase in most clinic and ambulatory BP means and loads across load groups (all p < 0.05). There was only a trend for higher LVMI (p = 0.06) and reduced strain (p = 0.05) in low vs high load groups. Diastolic function (E/e') was lower in high vs low and mid groups and there was a graded increase in arterial stiffness (PWV) across load groups. Daytime SBP load was an independent determinant of all forms of TOD after adjusting for age and sex but lost significance for LVMI after adjusting for BMI%. Load remained a significant determinant of PWV & E/e' after adjusting for BMI% and mean daytime ambulatory SBP. Load group was also a significant determinant of PWV and E/e' even after adjustment for age, sex, BMI% and daytime ambulatory SBP (all p < 0.0001). Conclusions: Daytime SBP load adds to prediction of diastolic dysfunction and arterial stiffness but not LVMI or systolic function. Increased load on ABPM may indicate need for advanced imaging to detect early TOD in youth with HTN.